New insights into the funerary rituals of the Neolithic site of Passo di Corvo (Apulia, Italy): The study of the human remains. (December 2020) - Mariotti, Valentina; Muntoni, Italo M.; Belcastro, Maria Giovanna
Highlights: The Passo di Corvo Neolithic village (VI millennium BC, Italy) yielded 12 burials. Human skeletal remains consists of bones from the inhumations and scattered bones. The burials were identified as primary inhumations by the excavators. We observed intentional peri mortem lesions (cut and scrape marks) on some bones. We demonstrated that treatment of the cadaver took place at Passo di Corvo. Abstract: In the present study we analyse the human skeletal remains of 10 of the 12 inhumations brought to light in the Neolithic ditched village of Passo di Corvo (VI millennium B.C., Foggia, Apulia, Italy), excavated between 1966 and 1980. The burials were identified as primary inhumations during the excavations, but we observed intentional peri mortem lesions (cut, chop and scrape marks) on some of the bones, attesting practices of defleshing and possibly of dismemberment. These findings indicate that the funerary rituals of the Neolithic people of Passo di Corvo included cadaver treatment practices that were impossible to postulate without a careful observation of the bones. This study highlights the importance of anthropological analysis even in the case of apparently clear contexts.